Solvothermal synthesis of CdIn2S4 photocatalyst for selective photosynthesis of organic aromatic compounds under visible light - Cancan Ling (Nature Portfolio, 2017)
Abstract Ternary chalcogenide semiconductor, cadmium indium sulfide (CdIn2S4), was prepared by a simple solvothermal method using ethylene glycol as a solvent, as well as indium chloride tetrahydrate (InCl3 .4H2O), cadmium nitrate tetrahydrate [Cd(NO3)2 .4H2O], and thiacetamide (TAA) as precursors. The resulted sample was subject to a series of characterizations. It is the first time to use CdIn2S4 sample as a visible light-driven photocatalyst for simultaneous selective redox transformation of organic aromatic compounds. The results indicate that the as-synthesized CdIn2S4 photocatalyst not only has excellent photocatalytic performance compared with pure In2S3 and CdS for the selective oxidation of aromatic alcohols in an oxygen environment, but also shows high photocatalytic redox activities under nitrogen atmosphere. A possible mechanism for the photocatalytic redox reaction in the coupled system was proposed. It is hoped that our current work could extend the applications of CdIn2S4 photocatalyst and provide new insights for selective transformations of organic compounds.